iSpeak: Public Speaking for Contemporary Life, 2008 Edition - E. Nelson Paul (Mc Graw Hill, 2009)
For your classes in Public Speaking McGraw-Hill introduces the latest in its acclaimed M Series. The M Series started with your students. McGraw-Hill conducted extensive market research with over 4,000 students to gain insight into their studying and buying behavior. Students told us they wanted more portable texts with innovative visual appeal and content that is designed according to the way they learn. We also surveyed instructors, and they told us they wanted a way to engage their students without compromising on high quality content.